1978
DOI: 10.1515/cclm.1978.16.8.447
|View full text |Cite
|
Sign up to set email alerts
|

Ein NH 4 + -selektiv-enzymatisches Durchflußsystem. Verfahren zur kontinuierlichen enzymatischen Elektroanalyse von Harnstoff, II. Mitteilung

Abstract: Zusammenfassung: Es wird ein Durchflußsystem zur NH^-selektiv-enzymatischen Harnstoffbestimmung beschrieben, bei der mit löslicher Urease schwimmend eine Harnstoff Spaltung erfolgt und die NH 4 " h -Freisetzung sekundär mit einer ammoniumselektiven Disk-Elektrode erfaßt wird. Als aktive Komponente für die Elektrodenmembran wurde das Carrier-Antibiotikum Nonactin in eine Polyvinylchlorid-Matrix inkorporiert. A NH^-selective-enzymatic flow-through system. A method for the continuous enzymatic, electrochemical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(4 reference statements)
0
4
0
1
Order By: Relevance
“…In particular, designing the tetrahedral symmetry of the binding site, with a coordination number of four, may play a key role in facilitating the binding of NH 4 + with respect to K + : indeed, K + is characterized by spherical symmetry and the preference for ionic bonds with coordination number of six or more. 26,27,80 One example of the described strategy was presented in the study by Graf et al 81 complex with electrostatic interactions. X-ray analysis revealed that NH 4 + was effectively placed at the center of a tetrahedron formed by the four nitrogen atoms of the receptor.…”
Section: Ammonium-selective Electrodes Based On Ionophores Different mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, designing the tetrahedral symmetry of the binding site, with a coordination number of four, may play a key role in facilitating the binding of NH 4 + with respect to K + : indeed, K + is characterized by spherical symmetry and the preference for ionic bonds with coordination number of six or more. 26,27,80 One example of the described strategy was presented in the study by Graf et al 81 complex with electrostatic interactions. X-ray analysis revealed that NH 4 + was effectively placed at the center of a tetrahedron formed by the four nitrogen atoms of the receptor.…”
Section: Ammonium-selective Electrodes Based On Ionophores Different mentioning
confidence: 99%
“…24,25 This preference could be attributed to the ad hoc properties of nonactin when binding with NH 4 + . [26][27][28][29] Nevertheless, both ionic size and monovalent charge of K + are competitively suitable with the receptor site features of nonactin. 26 Consequently, the presence of K + in the matrix in which NH 4 + needs to be measured represents an interference that sometimes-depending on the nature of the sampleimpedes the reliable detection of NH 4 + using ISEs based on nonactin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schindler et al (184) developed an ammonium ion-selective enzymatic flowthrough system for the measurement of urea concentrations. A selective disk electrode was used to measure the NH4+ liberated by urease.…”
Section: Nitrogenmentioning
confidence: 99%
“…Bei NH 4 + -selektiv-enzymatischer Harnstoffanalyse muß der Substratumsatz durch die immobilisierte Urease im hydrophilen Membrananteil ausreichend hoch sein, so daß selbst bei physiologisch niedrigem Harnstoffpegel des Blutes die hohe Querempfindlichkeit für K* des Carrier-Antibiotikums Nonactin ausreichend kompensiert ist [37,38], Dies ist bei unserem Membranaufbau gegeben. Die geringen Unterschiede in den lonenradien von NK^r^n 1,48 · 10~1 0 m) und K + fron l,33-10~* 10 m) bedingen die für diese Ionen aufallend große Querempfindlichkeit von ionenselektiven Elektrodenmembranen mit den Carrier-Antibiotika Nonactin und Valinomycin.…”
unclassified